Making Sense of Norms and Ethics in a Decentralised System, Review Essay of Mervyn Frost, Global Ethics: Anarchy, Freedom, and International Relations (London and NY: Routledge, 2009); Thomas Weiss, Humanitarian Intervention: Ideas in Action (Cambridge) - Betti, Andrea (My University)
Reseña de Mervyn Frost, Global Ethics: Anarchy, Freedom, and International Relations (London and NY: Routledge, 2009); Thomas Weiss, Humanitarian Intervention: Ideas in Action (Cambridge, UK and Malden, MA: Polity Press, 2007) and Benjamin N. Schiff, Building the International Criminal Court (Cambridge: Cambridge University Press, 2008). Estos libros tratan desde perspectivas diferentes de la relación entre normas internacionales e sistema internacional anarquico y basado en los intereses nacionales.

Book review of Mervyn Frost, Global Ethics: Anarchy, Freedom, and International Relations (London and NY: Routledge, 2009); Thomas Weiss, Humanitarian Intervention: Ideas in Action (Cambridge, UK and Malden, MA: Polity Press, 2007) and Benjamin N. Schiff, Building the International Criminal Court (Cambridge: Cambridge University Press, 2008). These books explore from different perspectives the relationship between international norms and anarchical international system based on national interests.
Artículos en revistas